Optimalisasi Sertifikasi Indikasi Geografis untuk Penguatan Ekonomi Lokal dalam Rantai Pasok Kopi Robusta Kota Sungai Penuh - Afdhal Chatra; Silvia Rahayu; Rio Baviga (Agrifo : Jurnal Agribisnis Universitas Malikussaleh, 2026)
This study aims to determine  the existing  condition of the robusta coffee supply chain performance in Sungai TFull City after Geographical Indication certification, analyze the robusta coffee marketing margin in each marketing channel involving coffee farmers, collecting traders, and Small and Medium Industries (SMEs) and find out  the existing conditions The research method uses quantitative and qualitative descriptive approaches involving 268 farmers, 19 collectors, and 15 coffee small and medium industry players (SMEs). Data were analyzed through the identification of marketing channels, calculation of marketing margins, and farmer's share, as well as qualitative descriptive analysis of the use of IG certification. The results of the study show that there are two main marketing channels, namely Channel I (farmers-collector traders– small and medium industries (SMEs) coffee) and Channel II (farmers– small and medium industries (SMEs) coffee). Farmer's share on Channel I is only 7.69%, while on Channel II it reaches 38.46%. Margin analysis shows that the Small and Medium Coffee Industry (SMEs) control around 66.7% of the total margin, reflecting the weak bargaining position of farmers. However, IG certification improves product reputation and opens up wider market access, but its utilization is not optimal because the use of the IG logo is not consistent and the economic benefits have not been evenly distributed, especially at the farmer level. This study concludes that IG certification has not had a significant impact on improving the welfare of farmers due to the weak internalization of IG values and institutional strengthening. Strengthening farmer organizations, vertical integration of supply chains, and sustainable policy support is needed so that the benefits of IG certification can be distributed fairly and sustainably.